SOSIALISASI PENGARUH BEBAN NON LINER PADA PERALATAN LISTRIK RUMAH TANGGA DI KELOMPOK IKATAN KELUARGA EKA KENCANA MEDAN JOHOR - Sri Indah Rezkika; Samaria Chrisna; Sinta Marito Siagian (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This community service is based on previous research. The goal to be achieved from this service is to increase the understanding and knowledge of the community, especially in the XI Eka Kencana Family Association, Kelurahan Gedung Johor, Medan Johor District regarding the use of electrical appliances in households which are non-linear loads. The low power factor results in power losses in the consumption of electrical energy in households, the electric power will be depressed and the work power decreases and the current usage increases in doing business. This service carried out group discussions in the use of electrical equipment, namely non-linear loads on households that can cause current harmonics so that additional torque on the electromechanical type KWh meter uses a rotating induction disc. As a result, the disk rotation will be faster or there will be an error measuring KWh meter on the 5th and 7th harmonics, because the induction dish is designed to operate only at the fundamental frequency.